Future agents and treatment directions in multiple myeloma. Issue 1 (February 2014) - Ocio, Enrique M; Mitsiades, Constantine S; Orlowski, Robert Z; Anderson, Kenneth C
Abstract : The development of bortezomib and immunomodulatory agents resulted in a revolution in the treatment of multiple myeloma (MM). Moreover, second-generation proteasome inhibitors (carfilzomib) and immunomodulatory agents (pomalidomide) have recently been approved. Nevertheless, the incurability of this disease requires other drugs with different mechanisms of action to either prolong the survival of patients refractory to current therapies, or achieve cure. Active research has been done exploring the pathogenesis of MM and searching for novel, druggable targets. In this regard, some of these novel agents seem promising, such as monoclonal antibodies (anti-CD38 – daratumumab or anti-CS1 – elotuzumab) or the kinesin protein inhibitor Arry-520. Other agents under investigation are kinase inhibitors, signaling pathways inhibitors or deacetylase inhibitors. With so many novel agents under investigation, future therapy in MM will probably involve the combined use of the already approved drugs with some of those newly discovered.